2017
DOI: 10.1016/j.bbamcr.2016.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac inositol 1,4,5-trisphosphate receptors

Abstract: Calcium is a second messenger that regulates almost all cellular functions. In cardiomyocytes, calcium plays an integral role in many functions including muscle contraction, gene expression, and cell death. Inositol 1,4,5-trisphosphate receptors (IP3Rs) are a family of calcium channels that are ubiquitously expressed in all tissues. In the heart, IP3Rs have been associated with regulation of cardiomyocyte function in response to a variety of neurohormonal agonists, including those implicated in cardiac disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 109 publications
(168 reference statements)
1
27
0
Order By: Relevance
“…These findings indicate that IP3R-mediated Ca 2+ release and SERCA-mediated SR Ca 2+ uptake are one of the major compensatory mechanisms for Ca 2+ handling in human CMs when the RYR2 function is lost. Future studies should investigate whether IP3R-dependent mitochondrial Ca 2+ flux modulates spontaneous electrical activity in human RYR2 −/− -iPSC-CMs and whether IP3R-mediated nuclear Ca 2+ signaling is involved in the activation of nuclear signal transduction for CM survival (Garcia and Boehning, 2017). Previous studies demonstrated that the store-operated calcium entry (SOCE) is present in embryonic cardiomyocytes and induces significant rise in Ca 2+ entry when the depletion of SR Ca 2+ stores occurs (Huang et al, 2006;Avila-Medina et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that IP3R-mediated Ca 2+ release and SERCA-mediated SR Ca 2+ uptake are one of the major compensatory mechanisms for Ca 2+ handling in human CMs when the RYR2 function is lost. Future studies should investigate whether IP3R-dependent mitochondrial Ca 2+ flux modulates spontaneous electrical activity in human RYR2 −/− -iPSC-CMs and whether IP3R-mediated nuclear Ca 2+ signaling is involved in the activation of nuclear signal transduction for CM survival (Garcia and Boehning, 2017). Previous studies demonstrated that the store-operated calcium entry (SOCE) is present in embryonic cardiomyocytes and induces significant rise in Ca 2+ entry when the depletion of SR Ca 2+ stores occurs (Huang et al, 2006;Avila-Medina et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of the studies on the role of IP 3 Rs in hypertrophy have focused solely on IP 3 R-2, despite the fact that the other two isoforms are also expressed in the heart [8, 17, 20]. We now show that all three IP 3 R channels are expressed at readily detectable levels in cardiomyocytes in both rodent and human heart.…”
Section: Discussionmentioning
confidence: 68%
“…As such, it is still unclear whether IP 3 R channels are significant contributors to cardiac physiology and pathologic remodeling such as hypertrophy [19]. It has been shown that all three IP 3 R isoforms, at least at the mRNA level, are expressed in the heart of humans and mice [8, 20]. This opens the question of whether IP 3 R-1 and -3 are able to functionally compensate for IP 3 R-2 deficiencies in these models.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing numbers of IP 3 Rs and in particular 'leaky' IP 3 Rs , as would result from increased diastolic Ca 2+ concentration, lead to increased spark initiation frequency. This suggests that the increase in IP 3 R expression could be a compensatory mechanism to dyad uncoupling from electrical activity in disease [49].…”
Section: Model Assumptions and Their Implicationsmentioning
confidence: 97%